Improvements in Blood Pressure Among Undiagnosed Hypertensive Participants in a Community-Based Lifestyle Intervention, Mississippi, 2010 - Zoellner, Jamie (Centers for Disease Control and Prevention, 2014)
INTRODUCTION: Effective strategies are needed to reach and treat people who lack awareness of or have uncontrolled hypertension. We used data from a community-based participatory research initiative, Hub City Steps, to quantify the prevalence of undiagnosed hypertension and determine the relationship between hypertension status at baseline and postintervention improvements in blood pressure and health-related quality of life. METHODS: Hub City Steps was a 6-month preintervention–postintervention lifestyle intervention targeting hypertension risk factors. Outcome measures were collected at baseline, 3 months, and 6 months. Generalized linear mixed models were used to test for effects by time and hypertension status. RESULTS: Of the enrolled sample (N = 269), most were overweight or obese (91%), African American (94%), and women (85%). When considering hypertension status, 42% had self-reported diagnosis of hypertension (self-reported subgroup; 84% with antihypertensive medication use); 36% had no self-reported medical history of hypertension, but when blood pressure was measured they had a clinical diagnosis of prehypertension or hypertension (undiagnosed subgroup); and 22% had no self-reported or clinical hypertension diagnosis (no hypertension subgroup). From baseline to 6 months, systolic blood pressure significantly improved for participants with self-reported hypertension [8.2 (SD, 18.2) mm Hg] and undiagnosed hypertension [12.3 (SD, 16.3) mm Hg], with undiagnosed participants experiencing the greatest improvements (P < .001). Effects remained significant after controlling for covariates. Health-related quality of life significantly improved for all 3 hypertension subgroups, with no apparent subgroup differences. CONCLUSION: This study reveals advantages of a culturally appropriate community-based participatory research initiative to reach those with undetected hypertension and effectively improve blood pressure status and health-related quality of life.